An Overview of the Relevance of IgG4 Antibodies in Allergic Disease with a Focus on Food Allergens - Thomas A. E. Platts-Mills; Behnam Keshavarz; Jeffrey M. Wilson; Rung-chi Li; Peter W. Heymann; Diane R. Gold; Emily C. McGowan; Elizabeth A. Erwin (MDPI AG, 2021)
Antibodies of the IgG4 isotype are strongly associated with allergic disease but have several properties such as not precipitating with allergens, not activating complement and poor binding to Fcγ receptors that argue against a pro-inflammatory role. In keeping with that, IgG4 antibodies are a striking feature of the response to immunotherapy. In two naturally occurring situations IgG4 antibodies are common with low or absent IgE antibodies. The first example is children raised in a house with a cat and the second is eosinophilic esophagitis (EoE). In many population-based cohorts, the ownership of a cat in early childhood is associated with a decreased prevalence of a cat allergy at age 10. The second example (i.e., EoE) is a novel form of food allergy that is not mediated by IgE and is related to consuming cow's milk or wheat. In EoE, patients have IgG4 to milk proteins in high > 10 µg/mL or very high > 100 µg/mL titers. Enigmatically these patients are found to have deposits of IgG4 in the wall of their inflamed esophagus. The factors that have given rise to EoE remain unclear; however, changes in food processing over the past 50 years, particularly ultra-heat treatment and the high pressure homogenization of milk, represent a logical hypothesis.